UNDIRECTIONAL ROTATING ANTENNA POLARIZATION - Ilnitskiy, L. Ya.; Osama, Turabi (Problems of Informatization and Control, 2021)
An omnidirectional antenna with rotating polarization is considered, which provides omnidirectional reception in the horizontal plane, as well as reception of a signal with circular and linear polarization.